The dynamics of earnings in Germany: Evidence from social security records - Timm Bönke; Matthias Giesecke; Holger Lüthen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
This paper uncovers ongoing trends in idiosyncratic earnings volatility across generations by decomposing residual earnings auto-covariances into a permanent and a transitory component. We employ data on complete earnings life cycles for prime age men born 1935 through 1974 that covers earnings between 1960 and 2009. Over this period, the German labor market undergoes a heavy transformation and experiences strong deregulation, deunionization and a shift in employment from the industrial to the service sector. Our findings of increases in both components reflect the distinct phases of this transformation process. In magnitude, the transitory component increases most strongly in the early 1970s and the 1990s for young workers, whereas the permanent component displays the strongest increases for older workers in the early 1980 and the 2000s. Thus, the changes complicate the labor market entry for young workers while widening wage differences for established workers.
Keywords: D31; D33; H24; 330; Earnings dynamics; Life cycle; Earnings distribution; Inequality; Earnings volatility